The Influence of Regional Funding Capacity, Poverty, Human Development Index and Economic Development within a Review of Welfare Society System Model in South Sulawesi Province - Mediaty (International Journal of Advanced Science and Technology, 2020)
The aim of this study is conducted to examine the impacts local government performance on the economic growth, poverty levels, and the regional human development index in order to formulate appropriate policy recommendations to regional governments to encourage efficient and effective performance or financial capacity to improve the accountability of the local government of in South Sulawesi. Data obtained in this research were descriptively analyzed and using path analysis in form of linear regression test. Findings are descriptive analysis on data related to regional financial performance variables and model of the community welfare system are presented. Locally-Generated Revenue (LGR) performance analysis was carried out to improve quality of regional financial management. Besides improving quality of regional financial management, regional revenue performance analysis also assessed effectiveness of regional autonomy. Some programs are currently being simultaneously implemented including affordable housing program, free health service and education for families under poverty line. These last two programs are funded from the transfer of fuel oil (BBM) subsidies. Programs are closely related and determined by financial capacity/money, thus they are not separated from the State budget or regional budget. The originality of this research is the measurement model of local government performance with a path analysis approach to economic growth, and poverty, as well as the human development index, it is deemed necessary to assess the performance of local governments in South Sulawesi Province, and is expected to provide a reference to improve local government performance. Keywords: Financial Performance, Economic Growth, Human Development Index, Poverty